Metoda określania ryzyka uszkodzenia drzewostanu przez wiatr - Bruchwald, Arkadiusz; Dmyterko, Elżbieta (Leśne Prace Badawcze, 2010)
The project has developed models of damage risk to tree stands by wind. The models take into consideration the following groups of factors: varied and constant stand characteristics, location of forest district representing location of stand within country regions, where damages occurred in the past. Five variable stand characteristics were taken into account, including average height, age, species composition, average tree taper (or more precisely – its inverse), and stand density. The average tree height plays the most important role in evaluation of risk – high tree stands have the biggest risk of damage by wind. The constant stand characteristics included only forest site type, but further research should also consider other factors, such as land relief. The coefficients for the risk models were obtained from the data received from multiple forest districts of Poland, especially those, where stands were damaged by the Kyrill storm in 2007 (Regional Directorates of the State Forests in Wrocław and Katowice). The risk models give the basis for the method presented in this paper. The work also uses information from the database of the Informatics System of the State Forests. Each stand is assigned the damage risk on the scale from 0 to 3. The higher risk value shows higher probability of damage to tree stand in case of strong wind occurrence. The models of risk of wind damage to tree stands require further improvement, including the more detailed calculation of risk coefficients related to tree species, forest site type, location of forest districts within country regions, and also consequences of previous wind damage occurrences. For the mountainous areas, it would be important to develop risk models, which take into account land relief. Key words: wind damages, risk models.